Nilai-Nilai Pendidikan Akhlak Dalam Al-Qur’an - Sri Waluyo (Al-Riwayah : Jurnal Kependidikan, 2018)
This paper discusses the content of Q.S. al-Baqarah ([2]: 67-73). The data used in the preparation of this paper is the data that is primary and secondary. The primary source is data obtained from the core source. In conducting a study of a verse, it is clear that the primary data source is derived from the Qur'an, precisely on Q.S. al-Baqarah ([2]: 67-73). Secondary data is data obtained from other sources that are still related to the problem and provide interpretation of the primary source. The method used in analyzing this paper is the tahlili method. This method describes the meaning contained by the Qur'an, verse by verse, and letter after letter according to the order in the Mushaf. The description includes the various aspects which the interpreted verses contain, such as the meaning of the vocabulary, the connotation of the sentence, the background of the verse down, its relation to other verses, both before and after. And do not miss the opinion that has been given regarding the interpretation of these verses, whether delivered by the Prophet, companions, the tabi'in, as well as other commentators. This study shows that in Q.S. (2): 67-73) there are values of moral education which include: 1) morals in asking, (2) morals to parents, (3) patience of educators, (4) educator honesty, and (5) obedience of learners.